2018
DOI: 10.1530/rep-17-0475
|View full text |Cite
|
Sign up to set email alerts
|

Siglec expression on the surface of human, bull and ram sperm

Abstract: Sialic acid (Sia) is a major constituent of both the sperm glycocalyx and female reproductive mucosal surface and is involved in regulating sperm migration, uterotubal reservoir formation and oocyte binding. Siglecs (sialic acid-binding immunoglobulin - like lectins) commonly found on immune cells, bind to Sia in a linkage- and sugar-specific manner and often mediate cell-to-cell interactions and signalling. Proteomic and transcriptomic analysis of human and bovine sperm have listed Siglecs, but to date, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…56 Sialic acid is a major constituent of glycocalyx on the spermatozoa surface, allowing them to survive as allogeneic cells in the female reproductive tract despite female immunity. 71 Ma et al (2016) 31 also highlighted that sialylation was important for mammalian sperm to mature and survive in the female uterus. Spermatozoa lacking of the major histocompatibility complex could escape the role of T cells, but are easily recognized by natural killer cells.…”
Section: Glycosylation Facilitates Sperm Survival In Female Uterus An...mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Sialic acid is a major constituent of glycocalyx on the spermatozoa surface, allowing them to survive as allogeneic cells in the female reproductive tract despite female immunity. 71 Ma et al (2016) 31 also highlighted that sialylation was important for mammalian sperm to mature and survive in the female uterus. Spermatozoa lacking of the major histocompatibility complex could escape the role of T cells, but are easily recognized by natural killer cells.…”
Section: Glycosylation Facilitates Sperm Survival In Female Uterus An...mentioning
confidence: 99%
“…While the truth is that healthy spermatozoa can usually fuse with eggs in addition to survival, evidence suggests that such survival mainly benefits from the glycans on the surface of spermatozoa . Sialic acid is a major constituent of glycocalyx on the spermatozoa surface, allowing them to survive as allogeneic cells in the female reproductive tract despite female immunity . Ma et al (2016) also highlighted that sialylation was important for mammalian sperm to mature and survive in the female uterus.…”
Section: Role Of Glycosylation In Semen Functionsmentioning
confidence: 99%
“…The role of sialic acid in impairing sperm transit through the cervix of Suffolk ewes may be mediated through the binding of spermatozoa to cervical mucins via a sialic-acid-recognizing protein on the sperm surface (Ma et al 2016, Alkhodair et al 2018, thus causing them to become attached to the large mucin glycoproteins. To block the sialic-acidrecognizing receptor on the sperm head from binding to cervical mucins we added free sialic acid, in the form of the trisaccharide 6′-sialyllactose, to either cervical mucus or ram spermatozoa and performed a mucus penetration test.…”
Section: Gene/breedmentioning
confidence: 99%
“…[ 17 ] showed that the addition of free sialic acid (6′-sialyllactose (Neu5Ac- α -2,6-Gal- β -1,4-Glc)) increased the ability of sperm to penetrate the ovine cervical mucus in vitro . This demonstrates that sperm become attached to the sialic acid of the large mucin glycoproteins, which may be mediated via a sialic-acid-recognizing protein on the sperm surface [ 29 , 30 ]. Thus the addition of free sialic acid blocked the sialic-acid-recognizing receptors on the sperm surface thereby preventing sperm from binding to the sialic acid of the cervical mucins.…”
Section: Discussionmentioning
confidence: 99%